A Bibliometric Analysis of the Hotspots Concerning Stem Cell Extracellular Vesicles for Diabetes in the Last 5 Years - Qiu, Haiyuan; Guo, Rong; Zhang, Yuanwen; Ying, Jianghui; Yan, Yazhou; Xiong, Jiachao (Frontiers in Public Health, 2022)
Background: Diabetes mellitus (DM) is a metabolic disease that endangers human health, and its prevalence is exploding and younger. Stem cell-derived extracellular vesicles (SC-EVs) have a repair function similar to SCs and no risk of tumor formation, which have been widely used in the repair of DM and its complications. We aim to map the hot trends of SC-EVs for the treatment of DM and providing directions for future research. Methods We screened all relevant publications on SC-EVs for DM from the Web of Science (Wos) during 2017–2021, and research trends in this field were analyzed by VOSviewer and CiteSpace. Results A total of 255 articles related to SC-EVs for DM were screened out according to the search strategy. China (122 publications and 2,759 citations) was the most productive country, followed by the USA (50 publications and 1,167 citations) and Italy (16 publications and 366 citations). The top five institutions with the most publications were located in Italy and China, with Turin University being the most productive. The journals Stem Cell Research and Therapy and International Journal of Molecular Sciences published most of the studies on SC-EVs for DM. ASHOK KUMAR published the majority of articles in this field, while QING LI was the most cited. Cluster analysis indicated that the current research trend is more focused on the repair mechanism and clinical translation of exosomes and their related preparations in promoting DM and its complications. Conclusion In this study, a comprehensive summary and analysis of the global research trends of SC-EVs used in DM and its complications was performed. In the past 5 years, relevant high-quality publications in this field have increased significantly, and SC-EVs have a good prospect for development in the treatment of DM and its complications.